Effects of andrographolide on lipopolysaccharide‐induced serum biochemical indices, immune responses and intestinal inflammation related to gene expression of Monopterus albus. (7th May 2021) - Shi, Yong; Zhong, Lei; Zhong, Huan; Liu, Yanli; Zhang, Junzhi; Wei, Zehong; Che, Changbao; Hu, Yi
Abstract: An 8‐week trial investigated how andrographolide effected lipopolysaccharide (LPS)‐induced serum biochemical indices, immune responses and the intestinal inflammatory response of Monopterus albus . The study included control and andrographolide groups (150 mg/kg andrographolide) with three replicates per group. Samples were taken 0, 3, 6, 12, 24 and 48 h after LPS injection. The results showed that the levels of GLU, COR, AST, ALT, IgM, LZM, AKP, C3 and C4 in serum showed an initial increasing that then decreased. Compared with that of the control group, the levels of serum LZM, AKP, IgM, C3 and C4 in the andrographolide group increased quicker after LPS injection, while the levels of GLU, COR, AST and ALT increased more slowly; further, these indices recovered to normal levels quicker. The expression of several genes in the intestine first increased and then decreased after LPS injection. Compared with that of the control group, il‐10, tgf‐β1, tgf‐β2 and tgf‐β3 gene expression in the andrographolide group increased quicker after LPS injection, while that of il‐1β, il‐8, il‐12β, nf ‐ κb, tlr‐3, tlr‐7 and tlr‐8 increased more slowly; these indices recovered to normal levels more quickly. In conclusion, LPS injection induced immune stress and inflammatory response in M . albus . Dietary supplementation with 150 mg/kg andrographolide effectively alleviated these responses.